Short proofs of some extremal results II - Conlon, D; Fox, J; Sudakov, B (Elsevier, 2015)
We prove several results from different areas of extremal combinatorics, including complete or partial solutions to a number of open problems. These results, coming mainly from extremal graph theory and Ramsey theory, have been collected together because in each case the relevant proofs are quite short.